Peran Citizen Journalism Dalam Memberikan Informasi Tentang Kota Bengkulu Pada Akun Instagram @Bengkuluinfo - Fenny Kurniasih; Dewi Kurniawati (Jurnal Ilmiah Wahana Pendidikan, 2023)
Technological advances have made citizen journalism also develop very rapidly, because many media use citizen journalism as a source of news and information. In addition to mass media, citizen journalism also uses social media as a platform to receive and disseminate information. The @bengkuluinfo account is one of the accounts that uses citizen journalism as a source of information. This study analyzes the role of citizen journalism in generating information about @bengkuluinfo accounts using a descriptive qualitative paradigm based on postpositivism. Data collection techniques were carried out by conducting interviews with two key informants and five informants and observations. The theory used in this study is the role theory of Tony Rodgers and the stages of the concept of initiation of citizen journalism. This research found that the role of citizen journalism is very important to provide information about the city of Bengkulu on @bengkuluinfo Instagram account, because it can help the audience to get information easily, quickly and in real time.